MAKNA SIMBOL TARI DHURAN SEBAGAI UPACARA PUNCAK PROSESI ADAT MASYARAKAT DAYAK SIANG DI KALIMANTAN TENGAH - Danah Norani; Juli Natalia Silalahi; Abdullah Abdullah (Journal SOSIOLOGI, 2020)
ABSTRACT This article describes the symbols and meanings contained in the Dhuran Dance movement. The purpose of this article to describe the symbols and meanings of motion in the Dhuran Dance at the Peak Ceremony of the Dayak Siang Traditional Procession. This study uses the Theory of Symbols and Meanings as a reference. The method used is qualitative research with a descriptive approach. The researchers concluded that in Dhuran Dance there were only a few movements which contained elements of symbols and meanings. See as a whole then illustrated the symbolic meaning contained in the motion, namely the symbolization of the spirit of gratitude to God and the attitude of democracy, togetherness of harmony, strong closeness in the Dayak Siang Tribe, with the offerings given by the community.